Literasi Digital terhadap Sikap Kewarganegaraan Siswa di Era Digital - Abdul Wahab; Ridwan (Jurnal Kependidikan Media, 2026)
The development of digital technology has changed the way students interact, access information, and participate in social life. In this context, digital literacy is an important competency that affects the formation of students' civic attitudes. This study aims to analyze the relationship between digital literacy and students' civic attitudes through the Systematic Literature Review (SLR) approach. The SLR process is carried out by following the PRISMA guidelines, including identification, screening, eligibility, and inclusion, to obtain relevant articles published between 2020 and 2025. The results of the study show that digital literacy plays a significant role in improving students' critical thinking skills, social participation, ethical awareness, and civic skills. In addition, digital literacy that is integrated into Pancasila and Citizenship Education (PPKn) learning is able to strengthen students' civic disposition. However, there are still challenges, such as low information evaluation capabilities and lack of understanding of digital ethics. This research emphasizes the importance of strengthening digital literacy as a strategy to form an intelligent, critical, and responsible generation in the digital era.   References Ariandini, N., & Ramly, R. A. (2023). Penggunaan multimedia pembelajaran interaktif dalam meningkatkan hasil belajar siswa. Jurnal Kependidikan Media, 12(2), 107-116. Basariah, B., Ismail, M., Jumrawati, J., & Edi, M. G. P. (2025). Civic literacy siswa melalui pendidikan Pancasila di era digital. SILA. Chen, B., Wu, B., & Wang, N. (2022). Digital skills and social awareness in education. Computers & Education. https://doi.org/10.1016/j.compedu.2021.104366. Choi, M., Glassman, M., & Cristol, D. (2020). What it means to be a citizen in the internet age: Development of a digital citizenship scale. Computers & Education, 107, 100–112.https://doi.org/10.1016/j.compedu.2017.01.002 Doko, M. R., & Gaite, T. (2024). Literasi digital sebagai upaya peningkatan civic skills mahasiswa PPKn. CIVICA. https://doi.org/10.30598/civica.14.1.25-34. Falloon, G. (2020). From digital literacy to digital competence: The teacher digital competency framework. Educational Technology Research and Development, 68, 2449–2472.https://doi.org/10.1007/s11423-020-09767-4. Hidayat, T., et al. (2023). Pendidikan etika digital dalam membentuk karakter siswa. Jurnal Pendidikan Karakter. https://doi.org/10.21831/jpk.v13i1.67890. Jamil, M., Tariq, R., & Shami, P. A. (2022). Digital literacy and student engagement in learning. Education and Information Technologies. https://doi.org/10.1007/s10639-021-10774-5. Kim, M., & Choi, D. (2021). Development of youth digital citizenship through digital literacy. Computers & Education. https://doi.org/10.1016/j.compedu.2020.104224. Kitchenham, B., Brereton, P., Budgen, D., Turner, M., Bailey, J., & Linkman, S. (2009). Systematic literature reviews in software engineering – A systematic literature review. Information and Software Technology, 51(1), 7–15. https://doi.org/10.1016/j.infsof.2008.09.009 Lee, L. (2021). Digital media and civic engagement among youth. New Media & Society.https://doi.org/10.1177/1461444820905044. Lestari, S., et al. (2024). Integrasi literasi digital dalam kurikulum PPKn. Jurnal Teknologi Pendidikan. https://doi.org/10.21009/jtp.v26i1.78901. Ng, W. (2021). New digital technology in education: Conceptualizing professional learning. Springer. https://doi.org/10.1007/978-3-030-37758-9. Nugraha, I. A., Normansyah, A. D., & Cahyono, C. (2024). Pengaruh literasi digital terhadap keterampilan berpikir kritis peserta didik pada mata pelajaran PPKn. Triwikrama: Jurnal Ilmu Sosial. https://doi.org/10.6578/triwikrama.v5i1.5984. Page, M. J., McKenzie, J. E., Bossuyt, P. M., Boutron, I., Hoffmann, T. C., Mulrow, C. D., et al. (2021). The PRISMA 2020 statement: An updated guideline for reporting systematic reviews. BMJ, 372, n71. https://doi.org/10.1136/bmj.n71 Park, Y. (2022). Online behavior and digital citizenship among students. Journal of Educational Computing Research. https://doi.org/10.1177/07356331211052345. Paul, J., Lim, W. M., O’Cass, A., Hao, A. W., & Bresciani, S. (2021). Scientific procedures and rationales for systematic literature reviews (SPAR-4-SLR). International Journal of Consumer Studies, 45(4), O1–O16. https://doi.org/10.1111/ijcs.12695. Pertiwi, A., Pramudika, N. R., Isnaini, P., & Fikri, R. A. (2024). Membangun literasi digital peserta didik melalui pendidikan kewarganegaraan di era media sosial. Indonesian Journal of Law and Justice. https://doi.org/10.61476/trkqkx61. Rahayu, D. A., Ulum, B., & Putra, A. A. P. E. (2024). Literasi digital dalam pembelajaran PKn berbasis saintifik untuk penguatan civic disposition mahasiswa. Jurnal Media Informatika. https://doi.org/10.55338/jumin.v6i3.5804. Rahman, A., et al. (2023). Implementasi literasi digital di sekolah menengah. Jurnal Pendidikan Indonesia. https://doi.org/10.23887/jpi.v12i2.56789. Ramly, R. A., & Ayu, S. (2022). Pengaruh Media Sosial Terhadap Hasil Belajar Siswa. Jurnal Kependidikan Media, 11(3), 107-119. Sari, D. P., et al. (2023). Pengaruh pembelajaran digital terhadap nilai kewarganegaraan siswa. Jurnal PPKn. https://doi.org/10.20527/kewarganegaraan.v13i1.12345. Snyder, H. (2019). Literature review as a research methodology: An overview and guidelines. Journal of Business Research, 104, 333–339. https://doi.org/10.1016/j.jbusres.2019.07.039 Supriatna, M. N., & Atikah, C. (2023). Penguatan kewargaan melalui literasi budaya di era digital. Jurnal Pendas. https://doi.org/10.23969/jp.v9i4.19040. Wulandari, W., Rosdiawati, R., & Budi, N. A. (2024). Strengthening digital literacy based on civic values and ethical learning. CIVICS Journal. https://doi.org/10.36805/civics.v10i02.11225. Xiao, Y., & Watson, M. (2019). Guidance on conducting a systematic literature review. Journal of Planning Education and Research, 39(1), 93–112. https://doi.org/10.1177/0739456X17723971 Yusuf, M., & Prasetyo, A. (2022). Pengaruh media sosial terhadap sikap kewarganegaraan siswa. Jurnal Civic Education. https://doi.org/10.21831/jce.v6i2.45678.